Design of Organic Rankine Cycle (ORC) Power Plant Systems by Using Flat-Plate Solar Collector - Sutopo Purwono Fitri; Muhammad Badrus Zaman; Fahri Adib Azizi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2019)
electrical energy is the most used energy today in daily activities and industry is increasing. In rural areas that do not have electricity still exists in Indonesia. In this study, it can be used as an alternative power plant that can be used by the countryside. The system used in this study is the new types of power plants, namely the Organic Rankine Cycle (ORC) system. In connection with the problems stated above, through this research, an effort will be made to design an ORC power generation system. The ORC power plant system that will be designed utilizes solar energy sources and working fluids. Solar power is used to heat the heating fluid in the form of water. This heating water is used to vaporize the working fluid which can evaporate at low temperatures and high pressures. So that the working fluid gas can be used to rotate the turbine shaft and produce electrical energy through a generator. Simulation is done using energy system software. In addition to simulations, examples of manual calculations are also needed for validation. The simulation results of the ORC generating system design on the two working fluids produce the greatest power at the pump outlet pressure of 6 bar with Wnet of 13.61 kW and the smallest power is generated by the pump outlet pressure of 5.03kW. While the design simulation of the ORC generating system produces power close to 10 kW at the pump outlet pressure of 5 bars with 11.38 kW. The flat collector solar-plate system gets the energy that is useful for collectors of 191.92 W and an efficiency of 9.8%.